2005
DOI: 10.1161/01.atv.0000181744.58265.63
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycosylation End Products Might Promote Atherosclerosis Through Inducing the Immune Maturation of Dendritic Cells

Abstract: Objective-Both advanced glycosylation end products (AGEs) and dendritic cells (DCs) have been shown to play a causative role in atherosclerosis. However, whether they function interactively in the process remains uncertain. We therefore studied the effects of AGE-bovine serum albumin (AGE-BSA) on the maturation of DCs and the expressions of scavenger receptor-A (SR-A) and receptor for AGEs (RAGE) on DCs. Key Words: advanced glycosylation end products Ⅲ atherosclerosis Ⅲ dendritic cells Ⅲ immunity Ⅲ receptor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 27 publications
3
98
1
Order By: Relevance
“…5A). These findings were surprising because recent studies have noted that the RAGE ligand HMGB-1 is released from DCs and can contribute to DC maturation and function (21) after RAGE and/or TLR2, -4, and -9 engagement (13,19,(22)(23)(24). However, the data reported here reveal that RAGE Ϫ/Ϫ BMDCs and splenic DCs responded normally to TLR stimulation, up-regulating surface expression of both CD86 and MHC class II and secreting normal levels of immunostimulatory cytokines.…”
Section: Discussioncontrasting
confidence: 66%
“…5A). These findings were surprising because recent studies have noted that the RAGE ligand HMGB-1 is released from DCs and can contribute to DC maturation and function (21) after RAGE and/or TLR2, -4, and -9 engagement (13,19,(22)(23)(24). However, the data reported here reveal that RAGE Ϫ/Ϫ BMDCs and splenic DCs responded normally to TLR stimulation, up-regulating surface expression of both CD86 and MHC class II and secreting normal levels of immunostimulatory cytokines.…”
Section: Discussioncontrasting
confidence: 66%
“…Indeed, Price et al (58) observed a dosedependent inhibition of CD83 expression on DCs exposed to AGE peptide, associated with the loss of their capacity to stimulate primary proliferation of allogeneic T cells. In contrast, Ge et al (31) have shown that AGE induced a dose-and time-dependent maturation of DCs as indicated by the expression of CD83. This apparent discrepancy could be explained by the use in this study of anti-CD14 Ab-coated beads to purify monocytes and, above all, much higher AGE concentrations (up to 200 mg/l).…”
Section: Discussionmentioning
confidence: 83%
“…The best-characterized receptor for AGEs, RAGE, is expressed on many cells that are targeted by HIV-1, such as monocytes and macrophages (27,28), CD4 T cells, and dendritic cells (DCs) (29)(30)(31). In monocytes and DCs, RAGE activation leads to an increase in proinflammatory cytokines such as IL-1b or TNF-b (32), IFN-g, and several chemokines and growth factors (31,(33)(34)(35). Considering the contribution of these factors to HIV-1 infection, AGE-RAGE interactions are likely to impact the biology of HIV-1 infection in many ways.…”
mentioning
confidence: 99%
“…It has been well documented that AGE and its receptor (RAGE) axis is involved in the pathogenesis of cardiovascular disease due to oxidative stress and inflammatory responses (4)(5)(6)(7). Furthermore, impaired macrophage lipid metabolism directly participates in foam cell formation in diabetes (8,9).…”
Section: Introductionmentioning
confidence: 99%